Królewskie grobowce Hasmoneuszy w Modin. Wzorce grecko-rzymskie a sztuka żydowska w okresie drugiej świątyni - Maciudzińska-Kamczycka, Magdalena (Studia Europaea Gnesnensia, 2012)
The focus of this paper will be on reception of the greco-roman art by Jews of the late second temple period, from the Hasmonean time (second century b.c.e.) to the destruction of the Jerusalem temple in 70 c.e. in this period, we see the changing relationship between art and Judaism and the Jewish perception of the greco-roman architectural and artistic patterns. The Hasmonean royal tombs in Modi’in in israel, existing only in the writings of ancient authors, are reflective of the shifting boundary between art and idolatry within Jews situated themselves in greco-roman culture.